Introduction to special section on The U.S. IOOS Coastal and Ocean Modeling Testbed. Issue 12 (11th December 2013) - Luettich, Richard A; Wright, L. Donelson; Signell, Richard; Friedrichs, Carl; Friedrichs, Marjy; Harding, John; Fennel, Katja; Howlett, Eoin; Graves, Sara; Smith, Elizabeth; Crane, Gary; Baltes, Rebecca
Abstract : [1] Strong and strategic collaborations among experts from academia, federal operational centers, and industry have been forged to create a U.S. IOOS Coastal and Ocean Modeling Testbed (COMT). The COMT mission is to accelerate the transition of scientific and technical advances from the coastal and ocean modeling research community to improved operational ocean products and services. This is achieved via the evaluation of existing technology or the development of new technology depending on the status of technology within the research community. The initial phase of the COMT has addressed three coastal and ocean prediction challenges of great societal importance: estuarine hypoxia, shelf hypoxia, and coastal inundation . A fourth effort concentrated on providing and refining the cyberinfrastructure and cyber tools to support the modeling work and to advance interoperability and community access to the COMT archive. This paper presents an overview of the initiation of the COMT, the findings of each team and a discussion of the role of the COMT in research to operations and its interface with the coastal and ocean modeling community in general. Detailed technical results are presented in the accompanying series of 16 technical papers in this special issue.